(untitled) (Medico Legal Update, 2021)
Back Ground:- Audit of transfusion practices in pediatric patients was performed to study indications , clinical profile and whether transfusions were in accordance to guidelines. Objective:- to perform audit of transfusion practices , in order to study appropriate and inappropriate usage of different blood components in pediatric population. Results:- In present study it was observed that out of 62 packed red cells transfusions 35(56.45%) transfusions were found to be inappropriate. Among FFP transfusions out of 55 transfusions 11(20%) transfusions were observed as inappropriate . Most of inappropriate transfusions had bleeds but normal coagulogram. Among Platelet transfusions , three (16.6%) platelet transfusions, out of 18 transfusions were inappropriate and transfused mainly to raise the platelet count. Conclusion:-Most frequently transfused blood components are red cells in pediatrics . Inappropriate transfusion of blood components hinders the utility of this valuable resource , Thus it becomes necessary to conduct regular audit of blood component transfusion for optimum utilization.